Serdeczne idiomy w listach Wisławy Szymborskiej i Kornela Filipowicza - Wojda, Dorota (Przestrzenie Teorii, 2023)
The correspondence between Wisława Szymborska and Kornel Filipowicz, which has been published in the book Listy. Najlepiej w życiu ma Twój kot (2016), is interpreted in this paper as a love discourse with the use of private idioms. This creates a poetics of the cryptogram, enigmatic to others, yet clear to the correspondents who combine epistolography, applied arts, literature, and life into one whole. The main means of this poetics is the recontextualization in which the writers perform different roles and move between them. This is related to creating of the text as theatre, which characterizes Szymborska’s poetry in particular as a modern lyric of the mask and role. The violation of the borders between various fields of art and life is done in these letters through collages, stickers, and ready mades that engage not only mind but also body, allowing to hide feelings behind a masquerade, at the same time conveying what is inexpressible.